Repeated instant self-healing shape memory composites - Wang, Chang Chun (2013)
We present a shape memory composite which is made of two types of shape memory materials, namely shape memory alloy (SMA) and shape memory hybrid. This composite has repeated instant self-healing function by means of not only shape recovery but also strength recovery (over 80%). The activation of the self-healing function is triggered by joule heating the embedded SMA.